Phylogeny and Systematics of Sassafras (Lauraceae), an Interesting Genus with Disjunct Distributions in Eastern North America and East Asia - Yunyan Zhang; Jingbo Zhou; David Y. P. Tng; Shuang Wang; Ying Wang; Ye Peng; Hong Liu; Zhongsheng Wang (Plants, 2023)
The Lauraceae is a family of the order Laurales, with 2500–3000 species comprising 50 genera, mainly distributed in tropical and subtropical evergreen broad-leaved forests. Up to two decades ago, the systematic classification of the Lauraceae was based on floral morphology, but molecular phylogenetic approaches have made tremendous advances in elucidating tribe- and genus-level relationships within the family in recent decades. Our review focused on the phylogeny and systematics of Sassafras, a genus of three species with highly disjunct distributions in eastern North America and East Asia, whose tribe affiliation within the Lauraceae has long been controversial. By synthesizing information on the floral biology and molecular phylogeny of Sassafras, this review aimed to explore the position of Sassafras within the Lauraceae, and to provide suggestions and implications for future phylogenetic studies. Our synthesis highlighted Sassafras as a transitional type between Cinnamomeae and Laureae with a closer genetic relationship with Cinnamomeae, as revealed by molecular phylogenetic evidence, while it shares many similar characteristics with Laureae in morphology. We therefore discovered that several molecular and morphological methods should be concurrently considered to illuminate the phylogeny and systematics of Sassafras in Lauraceae.